Learning Cocos2d-JS game development : learn to create robust and engaging cross-platform HTML5 games using Cocos2d-JS /: learn to create robust and engaging cross-platform HTML5 games using Cocos2d-JS. ([2015]) - Feronato, Emanuele
No abstract available